Digital Transformation and Multi-Level Collaboration in Regional Tax Data Collection: A Case Study of Local Governments in Indonesia: Transformasi Digital dan Kolaborasi Multi-Level dalam Pendataan Pajak Daerah: Studi Kasus Pemerintah Daerah di Indonesia - Nisa, Farichatun; Tamrin, M. Husni (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
This study aims to analyze the contribution of digital transformation integration and multi-level government collaboration to improving the effectiveness of regional fiscal governance, with a case study on the collection of data on Rural and Urban Land and Building Tax (PBB-P2) in Jombang Regency. The approach used emphasizes the use of the E-SPOP application and GIS-based mapping system as the main instrument of digitalization, as well as synergy between Bapenda, sub-district governments, villages, and hamlet apparatus in supporting the data collection process. The results of the study show two main contributions: first, the expansion of the tax object database as indicated by the increase in verified data by 9.16%; second, fiscal administration efficiency through the acceleration of data collection and an increase in the average realization of PBB-P2 revenues by 13.5%. These findings strengthen the relevance of the Digital Governance, Socio-Technical Systems, and New Public Management approaches, respectively related to the role of technology, institutional readiness, and orientation to efficiency and accountability. The study also identifies replication challenges in other areas, such as infrastructure disparities and human resource capacity, but offers strategic opportunities through modular approaches and national regulatory support. Thus, the digitalization of regional taxation is proven to be not just a technical innovation, but as part of fiscal institutional reform that can be replicated to strengthen more adaptive, inclusive, and sustainable fiscal governance in various regions in Indonesia.